Multiple co-circulating HIV-1 subtypes in the Middle East and North Africa. (17th July 2015) - Rolland, Morgane; Modjarrad, Kayvon
Abstract : HIV-1 incidence has been increasing more rapidly in the Middle East and North Africa than in any other global region. Despite this trend, HIV epidemiology in the region remains poorly defined. We conducted an analysis of 3284 publicly available HIV-1 sequences from 15 countries in the Middle East and North Africa to better characterize the regional epidemic. A phylogenetic tree based on the reverse transcriptase gene revealed a complex mosaic of diverse HIV subtypes and circulating recombinant forms across the region. Abstract : Supplemental Digital Content is available in the text